Maternal and neonatal adverse outcomes in individuals with a prior cesarean birth who undergo induction at 39 weeks. (January 2022) - Uwanaka, Ogechukwu; Raker, Christina; Gupta, Megha; Bicocca, Matthew J.; Fishel Bartal, Michal; Chauhan, Suneet P.; Wagner, Stephen
Abstract: Objective: To compare the maternal and neonatal adverse outcomes among individuals with one or two prior cesarean deliveries who are induced at 39 weeks gestational age versus those that are expectantly managed. Methods: This was a population-based cross-sectional study using U.S. National Vital Statistics 2014–2018 period linked birth and infant death data. Cohorts were individuals with one or two prior cesarean deliveries who were induced at 39.0 to 39.6 weeks gestation or underwent delivery from 40.0 to 41.6 weeks gestational age from either spontaneous labor or induction. The primary outcome was a composite of maternal adverse outcomes: admission to the intensive care unit, transfusion, uterine rupture, or unplanned hysterectomy. The secondary outcome was a composite of neonatal adverse outcomes, including: 5-minute Apgar score <5, assisted ventilation for >6 h, neonatal seizures, or neonatal mortality (death within 27 days of birth). Results: Of 263, 489 women who met the inclusion criteria 21, 951 (8.3%) underwent induction at 39 weeks. The composite maternal adverse outcome was significantly higher in women who delivered at 40–41 weeks gestation when compared to the 39 week gestation induction of labor cohort (8.1 versus 9.4 per 1, 000 births; aRR 1.18; 95% CI 1.01–1.39). The overall rate of composite neonatal adverse outcome was 10.4 per 1, 000 live births. The composite neonatal adverse outcome was also significantly elevated among deliveries at 40–41 weeks gestation as well (8.6 vs. 10.8 per 1, 000 live births; aRR 1.31; 95%CI 1.12–1.53). Conclusion: In women undergoing trial of labor after cesarean, induction of labor at 39 weeks gestation was associated with fewer maternal and neonatal adverse outcomes when compared to delivery at 40–41 weeks gestation.